Soil Water Characteristics Curves (SWCC) of residual soils stabilized using emerging and novel bioinspired technique - Muttaqa Uba Zango; Mahadi Lawan Yakubu; Abubakar Sadiq Muhammed; Jodin Makinda; Abubakar Abdulkarim; Muhammad Tajuri Ahmad (Penerbit Akademia Baru, 2024)
The development of unsaturated soil mechanics stemmed from the inadequacies of classical soil mechanics in addressing the partial pore spaces found in real-world soil systems. Nevertheless, evaluating soil parameters under partial saturation demands considerable resources. Hence, the Soil-Water Characteristic Curve (SWCC) theory was introduced to simplify this. SWCC is extensively used in geotechnical engineering, water resources, and agriculture to predict unsaturated soil parameter systems. In geotechnical engineering, SWCC is vital for designing systems near the Earth's surface, like slopes, clay liners and foundations. Furthermore, most conventional soil improvement techniques raise significant environmental concerns. Thus, the crisis prompts the advent of environmentally friendly construction materials, often known as bio-mediated and bioinspired soil enhancement techniques, like Enzymatic Induced Calcite Precipitation (EICP). EICP is an emerging eco-friendly technique that employs a simple chemical compound that reduces carbon footprints, and a bioinspired technique that mimics the natural forming process was applied to stabilise tropical soil for SWCC determination. Using the pressure plate method, SWCC parameters were derived by subjecting EICP-treated soils to varying concentrations of cementation solutions (0 – 1.00 M). Results revealed that saturated water content θs, retention water content θr, and air entry value Ψa increased with higher cementation solution concentration. The values of θs, θr, and Ψa improved from 0.663, 0.23405, and 3.4832 at a concentration of 0 cementation solution to 0.701, 0.22864, and 7.7086, respectively, upon treatment with a 1.00 M cementation solution. Finally, it has been demonstrated that EICP can improve the SWCC parameters of residual soil. Thus, the EICP technique can be exploited to stabilise residuals to construct compacted clay liners.